2014
DOI: 10.1002/jsfa.6668
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea chelating peptides inhibit copper‐mediated lipid peroxidation

Abstract: BACKGROUND Transition metals produce radical oxygen species promoting lipid peroxidation processes that favor the development of cardiovascular and neurodegenerative diseases. In addition, the oxidation of lipids present in food may affect the quality of food products. Therefore antioxidants counteracting these metal pro‐oxidant effects may have high potential for the pharmacology and food industries. This study investigated the capability of peptide fractions purified from chickpea protein hydrolysate to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Jamdar et al (2010) reported that a higher degree of cleavage of peanut peptide bonds renders a hydrolysate with higher metal chelating activity. Similar observations have been reported by Torres-Fuentes et al (2014), who showed with CP fractions’ iron chelating activities and inhibition of the copper-mediated lipid oxidation process. In our experimental design, histidine that was the main amino acid present in CPH17 as well as leucine, tyrosine and phenylalanine (Table I) could be implicated in the metal chelating activity and in trapping peroxyl lipid radicals (Torres-Fuentes et al , 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Jamdar et al (2010) reported that a higher degree of cleavage of peanut peptide bonds renders a hydrolysate with higher metal chelating activity. Similar observations have been reported by Torres-Fuentes et al (2014), who showed with CP fractions’ iron chelating activities and inhibition of the copper-mediated lipid oxidation process. In our experimental design, histidine that was the main amino acid present in CPH17 as well as leucine, tyrosine and phenylalanine (Table I) could be implicated in the metal chelating activity and in trapping peroxyl lipid radicals (Torres-Fuentes et al , 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Transition metal ion chelators can sequester these ions and control their prooxidant activity. The ability of transition metal ion chelators to inhibit a biomolecule oxidation, especially lipid oxidation, has been investigated (Shahidi and others ; Gülçin ; Torres‐Fuentes and others ). Iron, the most abundant ion in meat, released from heme pigments and ferritin, may be an important catalyst in the oxidation of lipids and proteins (Min and Ahn ).…”
Section: Polyphenols As Antioxidants: Structure–activity Relationshipmentioning
confidence: 99%
“…The types of food proteins and enzymes directly affect the structure of PAs. Soybean protein [33][34][35], wheat protein [36], corn protein [37], rice protein [38] of plant origin and muscle protein [39,40], collagen [41], milk protein [42], egg protein [43] of animal origin have been used for the preparation of PAs. Additionally, the parameters of time, added amount, temperature and pH may affect the degree of hydrolysis (DH) of the substrate proteins, which further affect the size and amino acid composition of the obtained peptides [44,45].…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%